Ultra-sensitive detection of Mycobacterium leprae: DNA extraction and PCR assays. - Fernanda Saloum de Neves Manta; Thyago Leal-Calvo; Suelen Justo M Moreira; Brunna L C Marques; Marcelo Ribeiro-Alves; Patrícia S Rosa; José Augusto C Nery; Rita de Cássia Pontello Rampazzo; Alexandre Dias Tavares Costa; Marco Aurelio Krieger; Milton Ozório Moraes (Public Library of Science (PLoS), 2020)
Leprosy urgently needs a precise and early diagnostic tool. The sensitivity of the direct (bacilli staining, Mycobacterium leprae DNA) and indirect (antibody levels, T cell assays) diagnostics methods vary based on the clinical form. Recently, PCR-based M. leprae DNA detection has been shown to differentially diagnose leprosy from other dermatological conditions. However, accuracy can still be improved, especially for use with less invasive clinical samples. We tested different commercial DNA extraction kits: DNeasy Blood & Tissue, QIAamp DNA Microbiome, Maxwell 16 DNA Purification, PowerSoil DNA Isolation; as well as in-house phenol-chloroform and Trizol/FastPrep methods. Extraction was performed on M. leprae-infected mouse footpads and different clinical samples of leprosy patients (skin biopsies and scrapings, lesion, oral and nasal swabs, body hair, blood on FTA cards, peripheral whole blood). We observed that the Microbiome kit was able to enrich for mycobacterial DNA, most likely due the enzymatic digestion cocktail along with mechanical disruption involved in this method. Consequently, we had a significant increase in sensitivity in skin biopsies from paucibacillary leprosy patients using a duplex qPCR targeting 16S rRNA (M. leprae) and 18S rRNA (mammal) in the StepOnePlus system. Our data showed that the presence of M. leprae DNA was best detected in skin biopsies and skin scrapings, independent of the extraction method or the clinical form. For multibacillary patients, detection of M. leprae DNA in nasal swabs indicates the possibility of having a much less invasive sample that can be used for the purposes of DNA sequencing for relapse analysis and drug resistance monitoring. Overall, DNA extracted with the Microbiome kit presented the best bacilli detection rate for paucibacillary cases, indicating that investments in extraction methods with mechanical and DNA digestion should be made.